DAVID Y GOLIAT: RELACIONES ENTRE ESTADOS UNIDOS-COSTA RICA EN EL PERÍODO DE LA POSGUERRA FRIA - Furlong, William L. (2015)
Due to the various situations that are currentlyexperiencing, the world is in a stateof change and evolution. Also, the globaleconomy is in a restructuring process, whichdirectly affects international relations, that iswhy the United States is in a phase of changein international relations with Latin Americato bring guide relations between States andneglecting communism. The above situationwill be reviewed on the basis of relations betweenthe United States and Costa Rica.